Situbondo communal waste management study: Application of the anaerobic baffled reactor method at the Salafiyah Syafi'iyah Islamic boarding school - Rifaini, Intan; Noerhayati, Eko (Asian Journal Collaboration of Social Environmental and Education, 2024)
​​​Background: This study examines the planning of a communal wastewater treatment plant (IPAL) at the Salafiyah Syafi'iyah Islamic Boarding School, Situbondo Regency, using the Anaerobic Baffled Reactor (ABR) method. Methods: This study uses the ABR method supported by literature studies as the basis for the preparation of the writing. The study also involved observation and field observation. Findings: (1) the domestic wastewater discharge generated by 4.410 people or 74 rooms is 364.408 m³/day, while the non-domestic wastewater discharge is 0.20 m³/day, bringing the total wastewater discharge to 364.608 m³/day. (2) The ABR method was chosen because it has several advantages, such as relatively small land requirements, ease of construction, operation and maintenance, no need for electrical energy, and more efficient costs. (3) The dimensions of each ABR compartment were designed to be 11.4 m long, 2.3 m wide, and 2.6 m high, which ensures even distribution of wastewater and effective treatment. Conclusion: The three research results led to the author's understanding that the ABR method is a suitable and efficient solution for wastewater treatment at Salafiyah Syafi'iyah Islamic Boarding School. For further planning, it is recommended to conduct detailed calculations regarding the Wastewater Management System (WMS) and consider the use of alternative methods such as Constructed Wetland or Anaerobic Filter Reactor, especially considering the area of the pesantren which is surrounded by rice fields.  Novelty/Originality of this study: This study offers an innovative solution for wastewater treatment in Islamic boarding school environments by applying the Anaerobic Baffled Reactor (ABR) method. This study not only designs an efficient and cost-effective system but also considers the specific context of Islamic boarding schools, paving the way for applying environmentally friendly technologies in Islamic educational institutions.